2015
DOI: 10.1111/apt.13449
|View full text |Cite
|
Sign up to set email alerts
|

The safety and efficacy of nasobiliary drainage in the treatment of refractory cholestatic pruritus: a multicentre European study

Abstract: SUMMARY BackgroundPruritus is a common symptom associated with cholestatic liver diseases. To date only small single centre case series have suggested efficacy of nasobiliary drainage in relieving cholestatic pruritus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 23 publications
(61 reference statements)
2
51
1
2
Order By: Relevance
“…This might also explain why NBD did not lower or improve pruritus in our patient. Thus, in contrast to other cholestatic conditions for which NBD was shown to be successful in attenuating refractory cholestatic itch,2 this approach might fail in particular in the subgroup of BRIC patients with severe dysfunction of ABCB11 4, 5. Consistent with our data, a case series demonstrated that pruritus in patients with ABCB11 mutations is less likely to respond completely to partial external biliary diversion compared to carriers of ATP8B1 variants 6.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This might also explain why NBD did not lower or improve pruritus in our patient. Thus, in contrast to other cholestatic conditions for which NBD was shown to be successful in attenuating refractory cholestatic itch,2 this approach might fail in particular in the subgroup of BRIC patients with severe dysfunction of ABCB11 4, 5. Consistent with our data, a case series demonstrated that pruritus in patients with ABCB11 mutations is less likely to respond completely to partial external biliary diversion compared to carriers of ATP8B1 variants 6.…”
Section: Discussionsupporting
confidence: 86%
“…It is characterized by episodes of jaundice accompanied by severe cholestatic itch but no signs of chronic liver disease in the symptom‐free intervals. To date, no evidence‐based treatment strategy has been established, but ursodeoxycholic acid and rifampicin might be helpful and nasobiliary drainage (NBD) and extracorporeal blood purification represent rescue therapies for refractory pruritus 1, 2. Here, we report on a patient with NBD‐refractory BRIC type 2 who improved under plasma separation and anion absorption therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmapheresis significantly decreases pruritus even 90 days after termination of the therapy. A recent multicentre European study demonstrated that nasobiliary drainage, another invasive method of reducing pruritus, significantly decreases itch in patients with PBC, but the effect lasts for a shorter period. This difference may on one the hand suggest that blood purification is more efficient than nasobiliary drainage in decreasing pruritus.…”
Section: Discussionmentioning
confidence: 99%
“…So lässt sich Pruritus auf-grund einer extrahepatischen Obstruktion des Gallengangssystems e ektiv mittels einer endoskopischen Dilatation, ggf. mit Stentimplantation, sowie einer transkutanen oder nasobiliären Drainage behandeln [12][13][14] nen gastrointestinale Nebenwirkungen die Anwendung limitieren [19].…”
Section: Aktuelle Therapieunclassified